Caractéristiques et stock de carbone de la végétation ligneuse des systèmes d’utilisation des terres de la commune de Coumbacara (Kolda, Sénégal) - Diallo, Hassanatou; Coly, Ismaïla; Ly, Mamadou Ousseynou; Diouf, Mayécor; Faye, Aliou (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Forest degradation causes carbon loss and indirectly contributes to climate change. Thus, the objective of this study is to assess the contribution of land use systems in the commune of Coumbacara to climate change mitigation through an estimate of woody diversity and their carbon stock. Thus, an inventory of woody vegetation was carried out on 72 plots of 30 m x 30 m in the forests adjacent to the fields and 50 m x 50 m in the hut and bush fields. The measurements related to the total height (m), the diameter at breast height (DBH) ≥ 10 cm and the crown diameter (m) of individuals of woody species. In addition to the diversity of this vegetation, the dendrometric data collected made it possible to develop the structure of woody vegetation, to estimate aboveground and belowground biomass as well as carbon stocks using allometric equations. In the forests adjacent to the fields, Combretaceae (61.9%) and Mimosaceae (52.4%) dominate. The woody population of this land use system has a decreasing exponential type structure with a specific richness of 7.85 ± 3.48 species and a density of 4.92 ± 0.39 feet/ha. The carbon stored there rises respectively by 1.57± 0.19 tC/ha for the aboveground biomass and 1.58±0.57 tC/ha for the belowground biomass. At the level of bush fields and hut fields, Anacardiaceae and Malvaceae are the most frequent. These agroforestry systems have a decreasing exponential type structure for the bush fields and an irregular structure for the hut fields. The bush fields have a species richness of 3.31±1.82 against 1.63±1.09 species for the hut fields. The density there is 3.01±0.57 feet/ha (bush fields) and 1.89±0.65 feet/ha (home fields). In addition, the amounts of carbon stored in the aboveground biomass of these systems are respectively 1.05 ±0.3 tC/ha and 0.99 ±0.51 tC/ha for the bush and hut fields against 0. 51±0.37 tC/ha and 0.54±0.49 tC/ha for underground woody biomass.